Bacillus amyloliquefaciens: Harnessing Its Potential for Industrial, Medical, and Agricultural Applications—A Comprehensive Review - Imen Zalila-Kolsi (19368502) (2023)
Bacillus amyloliquefaciens, a Gram-positive bacterium, has emerged as a versatile microorganism with significant applications in various fields, including industry, medicine, and agriculture. This comprehensive review aims to provide an in-depth understanding of the characteristics, genetic tools, and metabolic capabilities of B. amyloliquefaciens, while highlighting its potential as a chassis cell for synthetic biology, metabolic engineering, and protein expression. We discuss the bacterium’s role in the production of chemicals, enzymes, and other industrial bioproducts, as well as its applications in medicine, such as combating infectious diseases and promoting gut health. In agriculture, B. amyloliquefaciens has demonstrated potential as a biofertilizer, biocontrol agent, and stress tolerance enhancer for various crops. Despite its numerous promising applications, B. amyloliquefaciens remains less studied than its Gram-negative counterpart, Escherichia coli. This review emphasizes the need for further research and development of advanced engineering techniques and genetic editing technologies tailored for B. amyloliquefaciens, ultimately unlocking its full potential in scientific and industrial contexts. Other Information Published in: Microorganisms License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/microorganisms11092215